Clinical predictors of treatment failure for diabetic foot infections: data from a prospective trial - Benjamin A. Lipsky; Peter Sheehan; David G. Armstrong; Alan D. Tice; Adam B. Polis; Murray A. Abramson (2007)
Abstract To aid clinicians in selecting the appropriate approach for treating patients with diabetic foot infections, we investigated whether any baseline clinical findings predicted an unfavourable clinical outcome. Using data from a large, prospective treatment trial of diabetic foot infections (SIDESTEP), we assessed the association between clinical treatment failure and baseline history, physical and laboratory findings, by univariate and multivariate logistic regression analyses. Among 402 patients clinically evaluable 10 days after completing antibiotic therapy, baseline factors significantly ( P < 0·05) associated by univariate analysis with treatment failure were ‘severe’ (versus ‘moderate’) University of Texas (UT) wound grade; elevated white blood cell count, C‐reactive protein or erythrocyte sedimentation rate; high wound severity score; inpatient treatment; low serum albumin; male sex; and skin temperature of affected foot >10°C above that of unaffected foot. By multivariate logistic regression only severe UT wound grade (odds ratio 2·1) and elevated white blood cell count [odds ratio 1·7 for a 1 standard deviation (2971 cells/mm 3 ) increase] remained statistically significant. Clinical failure rates were 46% for patients with both risk factors compared with 10% for patients with no risk factors and 16–17% for patients with one risk factor. Increased white blood cell count and severe UT wound grade at baseline, but not other features, were significant independent and additive risk factors for clinical failure in patients treated for a diabetic foot infection.